EXPLORING THE VIABILITY OF SERVICE ROBOTS IN PERFORMING HUMAN AESTHETIC LABOUR IN THE HOSPITALITY INDUSTRY - Elmohandes, Nirmeen; Pető, Károly (Economica, 2023)
This literature review seeks to investigate the value of human aesthetic labour in light of the growing deployment of robotic service workers. As automation continues to advance and replace human workers in a variety of industries, including service industries such as retail, hospitality, and entertainment, the role, value and the significance of aesthetics and the human touch grows. Due to the contemporary nature of the topic, researchers combed databases like Scopus, Web of Science, and Google Scholar for relevant articles using terms like "human aesthetic labour," "robotic service workers," and "service industry." This review will investigate the extent to which the rise of robotic service workers has altered the perception and value of human aesthetic labour. The findings of this research review will contribute to the ongoing discussion on the future of work in the service industry and provide businesses with insights on the significance of preserving human aesthetic labour and its impact on customer and guest experience as well as business performance.